Use Of Alternative Energy Sources in Telecommunication Stations - Juraev Nurmakhamad (Zien Journals, 2023)
The telecommunications industry plays a vital role in global connectivity, relying heavily on reliable and uninterrupted power supply to ensure seamless communication services. However, traditional energy sources, such as fossil fuels and grid electricity, have proven to be costly and environmentally unsustainable. This abstract discusses the emerging trend of utilizing alternative energy sources in telecommunication stations as a sustainable and economically viable solution to power challenges. Alternative energy sources, including solar photovoltaic systems, wind turbines, and energy storage technologies, are being increasingly adopted in telecommunication stations. These solutions have the potential to reduce operational costs, minimize carbon footprints, and enhance energy resilience.
Keywords: Telecommunication Stations; Alternative Energy Sources; Renewable Energy